Risk of Retinopathy of Prematurity Among Preterm with Neonatal Sepsis in a Tertiary Care Hospital a Prospective Study - Amir Afzal, Riffat Omer, Manjoor Kumar, Muhammad Naveed Khani, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the risk of retinopathy of prematurity (ROP) among preterm with and without sepsis admitted in a neonatal intensive care unit of a tertiary care hospital of Karachi, Pakistan. Methodology: In this prospective cross-sectional study conducted at Aga Khan University Hospital from October 2021 to March 2022. All the preterm born at gestation <32 weeks with birth weight of <1.5kg and were <28 days old of either gender was included. Examination for ROP was performed. Information about maternal and neonatal confirmed sepsis, risk factors predisposing to sepsis, ROP status were noted. Babies were followed in the outpatient clinics. The first examination was performed at 28th days and was subsequently followed at one or two week’s interval as per the Ophthalmologist. Results: Of 125 neonates, the mean age was 4.34 ±0.79 weeks. There were 72 (57.6%) males and 53 (42.4%) females. Stage 0 and 1 were most common stages reported as 49 (39.2%) and 55 (44%) neonates respectively. Zone 1 disease was observed in 15 (12.0%) whereas ROP plus disease in 7 (5.6%) neonates. Neonates with ROP stage <2 had significant association with maternal risk factors for sepsis (p-value 0.026), neonatal risk factors for sepsis (p-value 0.047), and neonatal culture proven sepsis (p-value 0.010). Similarly, zone 1 disease had a significant association with presence of maternal risk factors for sepsis (p-value 0.033), neonatal risk factors for sepsis (p-value 0.045), and antibiotics taken >48 hours (p-value 0.027). Conclusion: A considerably higher risk of ROP was observed among hospitalized neonates with neonatal sepsis. Keywords: Neonates, sepsis, retinopathy of prematurity, Preterm